Japanese plums (Prunus salicina Lindl.) and phytochemicals – breeding, horticultural practice, postharvest storage, processing and bioactivity. (6th March 2014) - Fanning, Kent J; Topp, Bruce; Russell, Dougal; Stanley, Roger; Netzel, Michael
Abstract Previous reviews of plum phytochemical content and health benefits have concentrated on the European plum, Prunus domestica L. However, the potential bioactivity of red‐ and dark red‐fleshed Japanese plums, Prunus salicina Lindl., so‐called blood plums, appears to warrant a significant increase in exposure, as indicated in a recent review of the whole Prunus genus. Furthermore, Japanese plums are the predominant plum produced on an international basis. In this review the nutrient and phytochemical content, breeding, horticultural practice, postharvest treatment and processing as well as bioactivity (emphasising in vivo studies) of Japanese plum are considered, with a focus on the anthocyanin content that distinguishes the blood plums. © 2014 State of Queensland Journal of the Science of Food and Agriculture © 2014 Society of Chemical Industry